2021
DOI: 10.3390/app11209375
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between the Number of Asphalt Mixing Plants and the Production of Asphalt Mixtures in European Countries and the Baltic States

Abstract: The transport infrastructure’s pavement is made of asphalt layers, placed and compacted. The asphalt mixture is produced in an asphalt mixing plant (AMP) using expensive technological equipment which, when it becomes obsolete and worn out, is replaced with new equipment. One of the main problems related to the replacement process is that when it comes to purchasing new AMPs, the decision making involved is, in most cases, highly intuitive due to a lack of clearly defined criteria. In order to remedy this situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…The authors found that engineers have analyzed and summarized the fault manifestations and troubleshooting methods of different types of CPSs used in different projects and different industries [32][33][34][35][36], which has a certain reference significance for similar system troubleshooting. However, there are many types of faults in CPSs, and there are no clear classification standards.…”
Section: Fault Classification For Cpssmentioning
confidence: 99%
“…The authors found that engineers have analyzed and summarized the fault manifestations and troubleshooting methods of different types of CPSs used in different projects and different industries [32][33][34][35][36], which has a certain reference significance for similar system troubleshooting. However, there are many types of faults in CPSs, and there are no clear classification standards.…”
Section: Fault Classification For Cpssmentioning
confidence: 99%